About “being caboclo”: the caboclos voices from the west Santa Catarina - Souza , Maria de; Bernardi , Luci dos Santos; Santos , Jorge Alejandro (Revista do Instituto de Estudos Brasileiros, 2020)
The present article intends to “tell” the caboclo culture of the western region of Santa Catarina, Brazil, aiming to identify and characterize elements of this ethnicity that mobilize the reconnaissance of the “being caboclo”. It is characterized as a qualitative study based on a documentary analysis made from the portfolio of interviews conducted by the Western Memory Center of Santa Catarina (CEOM) in 2006, which inventoried and safeguarded aspects of the caboclo immaterial culture of this region. Considering that the historical context has marginalized this ethnicity that sees its life forms being forgotten over time, we seek to provide the reconnaissance and appreciation of the caboclo culture of western Santa Catarina.